Moxifloxacin Based Triple Therapy as Alternative to Standard Therapy in Helicobacter Pylori Eradication - Ahmed, Mohammed H.; Abd-Elsalam, Sherief; Mahrous, Aya M. (Anti-Infective Agents, 2021)
Introduction: Helicobacter pylori eradication remains a problematic issue. We are in an urgent need for finding a treatment regimen that achieves eradication at a low cost and with less side effect. Recent published results have shown a high rate of resistance with clarithromycinbased treatment regimens. The aim of the study was to compare moxifloxacin therapy and classic clarithromycin triple therapy in H. pylori eradication. Methods: This was a pilot study that enrolled 60 patients with helicobacter pylori associated gastritis. Diagnosis was done by assessment of H. pylori Ag in the stool. The patients were randomly assigned to receive either moxifloxacin based therapy (Group A), or clarithromycin based therapy (Group B) for two weeks. We stopped the treatment for another two weeks and then re-evaluation for cure was done. Results: 90% of patients had negative H. pylori Ag in the stool after 2 weeks of stoppage of the treatment in group A versus 66.7% in Group B. None of the patients in both the groups had major side effects. Conclusion: Moxifloxacin-based therapy showed higher eradication power and less resistance when compared to clarithromycin triple therapy.
Keywords: Proton Pump Inhibitors (PPI)